Using thermosensitive radiotelemetry to document rest and activity in a semifossorial rodent - Stefanie E. Lazerte; Donald L. Kramer (Wildlife Society Bulletin)
Abstract We present a protocol for using temperature records from external thermosensitive radiotransmitters recorded by data‐logging receivers to identify bouts of rest and activity in mammals that sleep in a curled‐up posture. We illustrate the protocol using eastern chipmunks (Tamias striatus) sampled in the Ruiter Valley Land Trust near Mansonville, Quebec, Canada. Temperatures recorded at intervals of 12–45 min, when chipmunks were in their burrows as well as above ground, displayed sequences of warmer, stable temperatures (assumed to be produced by curled‐up, resting individuals) alternating with sequences of cooler, more variable temperatures (assumed to be produced by active individuals). By sampling points from typical sequences of rest and activity and using regression tree analyses to optimize the distinction between resting and active temperatures, we were able to define bouts of rest and activity. Torpor bouts were also identified by a distinct pattern of decreasing temperatures. Because curled‐up rest did not occur outside the burrow, we were able to validate the assignment of bouts by independent determination of chipmunk locations using handheld telemetry. The proportion of observations of chipmunks outside the burrow correctly classified as active and the proportion of chipmunks classified as resting that were correctly located in their burrows were both high (approx. 96%). For the numerous mammalian species that curl up to rest, continuously recorded thermosensitive telemetry has the potential to provide more precise and reliable data on rest and activity over longer periods, including the night and time in burrows or dens, and with less effort per individual than most alternative techniques. © 2011 The Wildlife Society.